Acute high‐altitude hypoxia exposure causes neurological deficits via formaldehyde accumulation. (18th May 2022) - Wang, Xiaoyin; Sun, Haochen; Cui, Lili; Wang, Xian; Ren, Changhong; Tong, Zhiqian; Ji, Xunming
Abstract: Introduction: Acute high‐altitude hypoxia exposure causes multiple adverse neurological consequences. However, the exact mechanisms are still unclear, and there is no targeted treatment with few side effects. Excessive cerebral formaldehyde (FA) impairs numerous functions, and can be eliminated by nano‐packed coenzyme Q10 (CoQ10). Aims: In this study, we aimed to investigate whether cerebral FA was accumulated after hypobaric hypoxia exposure, and further explored the preventative effect of CoQ10 through FA elimination. Results: Accumulated cerebral FA was found in C57BL/6 mice after acute high‐altitude hypoxia exposure, which resulted in FA metabolic disturbance with the elevation of semicarbazide‐sensitive amine oxidase, and declination of aldehyde dehydrogenase‐2. Excessive FA was also found to induce neuronal ferroptosis in vivo. Excitingly, administration with CoQ10 for 3 days before acute hypobaric hypoxia reduced cerebral FA accumulation, alleviated subsequent neuronal ferroptosis, and preserved neurological functions. Conclusion: Cerebral FA accumulation mediates neurological deficits under acute hypobaric hypoxia, and CoQ10 supplementation may be a promising preventative strategy for visitors and sojourners at plateau. Abstract : Proposed molecular mechanism of acute hypobaric hypoxia induced neurological deficits via formaldehyde accumulation. AHH, acute hypobaric hypoxia; MA, methylamine; SSAO, semicarbazide‐sensitive amine oxidase; FA, formaldehyde; ALDH2, aldehyde dehydrogenase 2; H2 O, water; CO2, carbon dioxide; GSH, glutathione; GPx4, glutathione peroxidase 4; LPO, lipid peroxidation; Fe 2+, ferrous iron.